Femoral artery-nourished anteromedial thigh flap: A new perspective in oral and maxillofacial defect reconstruction. (June 2021) - Gong, Zhaojian; Zhang, Shanshan; Li, Panchun; Liu, Jiang; Xu, Yuming
Highlights: FA-nourished AMT flap can be used to repair some oral and maxillofacial defects. FA-nourished AMT flap can be used as a new alternative to the ALT flap. FA-nourished AMT flap can be combined or separately used with the ALT flap. Abstract: Objectives: The aim of this study was to evaluate the feasibility and efficacy of the femoral artery (FA)-nourished anteromedial thigh (AMT) flap for reconstructing oral and maxillofacial defects. Patients and methods: The authors analyzed a retrospective case series of 13 patients who underwent the reconstruction of oral and maxillofacial defects with the FA-nourished AMT flap. The flap design and the methods for defect reconstruction are described, and the reconstructive efficacy is reported. Results: Of the 13 patients, 12 were men, and 1 was woman, with an average age of 52.2 years. Of these FA-supplied AMT flaps, 7 were singly used, 5 were combined with the anterolateral thigh (ALT) flap or its chimeric flaps, and 1 was separately used with the ALT flap. Postoperatively, all flaps survived completely, without vascular compromise or major wound complications. Conclusions: The FA-nourished AMT flap can also be used to reconstruct some common oral and maxillofacial defects, especially as a new alternative to the ALT flap. In addition, this flap can be combined with the ALT flap or its chimeric flaps or separately used with the ALT flap for the reconstruction of complex defects.